Biodegradation of Wastewater Oil Pollutants, Identification and Characterization: A Case Study - Galing River, Kuantan Pahang, Malaysia - Wan Faizal, Wan Ishak; Makky, Essam A.; Datusahlan, Mupit (IACSIT Press, 2013)
This research is aims to access the potential of natural occurring bacteria for pollutant degradation. The study was carried out in Galing River, Kuantan, Pahang. There were four sampling sites that were chosen along the river and the samples were analyzed to identify specific bacteria that useful for pollution control. The identification shows that different bacteria isolates were identified, mention as a positive (+) or negative (—). Screening for lipolytic activity by using Tween 20, Rhodamine B and phenol red was done. The results revealed that, the bacterial consortium in Galing River can be utilized as biodegradation agent. Screening using Tween 20 showed two areas were positive has lipolytic activity. However, screening using Rhodamine B, exhibited that all samples showed high positive lipolytic activity. While, phenol red, was positive only for two of the sampling points. Biodegradation studies showed, the bacteria could degrade the oil after 3 days incubation.